2020
DOI: 10.1111/btp.12816
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of phyllostomid bats in an urban–rural landscape: A scale‐dependent analysis

Abstract: Urbanization is one of the most pervasive processes of landscape transformation, responsible for novel selection agents promoting functional community homogenization. Bats may persist in those environments, but the mechanisms responsible for their adaptability and the spatial scales in which the landscape imposes environmental filtering remain poorly studied in the Neotropics. We tested the hypothesis that landscape composition interacts with the spatial scale to affect the functional diversity of phyllostomid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 102 publications
1
13
0
2
Order By: Relevance
“…Thus, they are thought to be better adapted to survive in deforested landscapes (Wordley et al 2017). These theoretical predictions have been empirically corroborated in several Neotropical locations (e.g., Meyer & Kalko 2008, Jung & Kalko 2010, Farneda et al 2015, Ramírez-Mejía et al 2020). However, most studies focused on the phyllostomid trait responses at the assemblage or trophic guild level (Gonçalves et al 2017, Brändel et al 2020, Farneda et al 2020), overlooking the potential intraspecific consequences of landscape transformation on bats’ ecomorphological traits.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, they are thought to be better adapted to survive in deforested landscapes (Wordley et al 2017). These theoretical predictions have been empirically corroborated in several Neotropical locations (e.g., Meyer & Kalko 2008, Jung & Kalko 2010, Farneda et al 2015, Ramírez-Mejía et al 2020). However, most studies focused on the phyllostomid trait responses at the assemblage or trophic guild level (Gonçalves et al 2017, Brändel et al 2020, Farneda et al 2020), overlooking the potential intraspecific consequences of landscape transformation on bats’ ecomorphological traits.…”
Section: Introductionmentioning
confidence: 57%
“…During the sampling, we recorded two recaptures in two LU, and both times, recaptured bats were found at their original LU. For additional details regarding sampling and the phyllostomid assemblage recorded see Ramírez-Mejía et al (2020). After correlation analyses, we excluded landscape collinear variables and retained grass cover at 0.5 and 2 km scales and forest percentage at 0.5 and 1.25 km (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Además, un número considerable de esas investigaciones se concentró en aspectos descriptivos de la diversidad taxonómica de los mamíferos en un lugar particular, y sólo un estudio publicado recientemente presentó resultados a nivel de paisaje para entender los efectos de la urbanización sobre la diversidad de mamíferos. En este caso, se encontró que la diversidad funcional de murciélagos filostómidos está afectada por la transformación del paisaje urbano-rural de Villavicencio y que el efecto de la composición del paisaje dependió de la escala (Ramírez-Mejía et al, 2020). Este tipo de análisis se une a otros trabajos que han resaltado las complejas respuestas de la biodiversidad ante los cambios en y alrededor de las ciudades, y que se relacionan con las particularidades de cada urbanización (Grimm et al, 2008;Beninde et al, 2015).…”
Section: Discussionunclassified
“…In these species their ear length and wingspan are relatively larger, in contrast to those of the large species Artibeus lituratus, found in CU-UNAH and Sabanagrande. Ramírez-Mejía et al [55] demonstrated that the most dominant functional group of bats in their studies were those with intermediate values of body mass and wing morphology, which represents the phyllostomids' adaptive response to landscape degradation.…”
Section: How Urbanization Is Affecting Bat Diversitymentioning
confidence: 99%
“…In general, phyllostomids have an early activity peak and then declining activity through the night [57]. Habitat specialization, nutrient intake, and food procurement are features that are associated with bat success in transformed landscapes [55,58].…”
Section: From Cities To Forests: Activity Patterns Of Phyllostomids Imentioning
confidence: 99%